A cuvette-compatible Zn2+ sensing tool for conventional spectrofluorometers prepared by copolymerization of macrocyclic fluoroionophores on quartz glass surface. (1st July 2022) - Golcs, Ádám; Kovács, Korinna; Vezse, Panna; Bezúr, László; Huszthy, Péter; Tóth, Tünde
Abstract: We report here the development of a surface-modified quartz glass sheet, which affords an opportunity for converting conventional spectrofluorometers to ion-selective optochemical sensors by placing it diagonally into a photometric cuvette. Moreover, we describe a generalizable technique, which allows the usage of any polymerizable ionophores for developing multiple-use fluorescent chemosensors of various selectivity. A fluorescent bis(acridino)-crown ether containing allyl groups was photocatalytically copolymerized with a methacrylate-acrylamide-based monomer mixture to obtain an ion-selective sensor membrane layer on the surface of the cuvette-compatible glass sheet. This glass membrane-based direct optode enabled the analysis of Zn 2+ above a lower limit of detection of 2.2 × 10 –7 mol·l −1 with an excellent reusability. Limiting factors, like pH and competing ionic or organic agents were thoroughly investigated. Moreover, spiked river-water samples were measured to demonstrate applicability. The proposed sensor placed in any conventional spectrofluorometer provides an innovative method for perturbation-free analysis of Zn 2+ for all the chemists in need of a fast, easy-to-use, portable and regenerable analyzer without the requirement of an analyte-specific instrumentation.